How to monitor and influence the EU decision-making process from a trade union perspective - Pennella, Silvana (Brussels, 2013)
" This training manual aims to provide trade union representatives with the necessary information and guidelines to enable them to influence the decision-making process of the European Union. Its objective is to help trade union representatives monitor and influence the EU decision-making process. Its content is based on an exchange of lobbying experiences from different stakeholders, among others, Members of the European Parliament, European Commission officials, representatives of European Trade Union Federations and NGOs."